Plasma soluble factor following two decades prolonged suppressive antiretroviral therapy in HIV-1-positive males: A cross-sectional study. Issue 5 (February 2018) - Sperk, Maike; Zhang, Wang; Nowak, Piotr; Neogi, Ujjwal
Abstract : Abstract: Acute human immunodeficiency virus (HIV) infection is associated with a marked induction of several pathways that are linked to inflammation and CD4 + T-cell depletion. Many of these processes do not fully resolve on short-term combination antiretroviral therapy (cART) (<5 years), despite complete and durable suppression of viremia. The effects of long-term (>15 years) successful antiretroviral therapy (ART) and the linkage between levels of biomarkers remain unclear. Therefore, the present study aims to assess the host plasma proteome in a well-defined clinical material from HIV-1-positive male patients on successful long-term ART (>15 years) and compared them with age-matched healthy controls and treatment-naïve male patients with viremia in a cross-sectional manner. Plasma samples were obtained from 3 categories of age-matched HIV-1-positive male patients on long-term successfully (ART, n = 10) with a median (Interquartile range, IQR) of 19 (17–20) years, treatment-naïve patients with viremia (VP, n = 14), and HIV-1-negative persons (HC, n = 11). Plasma proteome was analyzed using the proximity extension assay targeting 92 factors. Statistical analyses were performed with GraphPad Prism v7, R-packages, and Qlucore Omics Explorer v3.2. Functional enrichment analysis was performed by Kyoto Encyclopedia of Genes and Genomes (KEGG), and interactions of specific molecules were identified using Path Designer integrated into Ingenuity Pathway Analysis (IPA). Group wise comparison identified 53 soluble factors, which differed between the groups ( P  < .05). Cluster analysis identified 13 discrete soluble factors (CD8A, CRTAM, CXCL13, EGF, CD5, CD40, CXCL9, Gal-1, IL12RB1, KLRD1, PD-1, CASP-8 and TNFRSF9) between the studied groups (adjusted P  < .001). The long-term successfully ART-treated individuals clustered and networked with the HC while VPs clustered separately. All of the proinflammatory cytokines and chemokines were normalized back to levels of healthy controls in long-term successfully ART-treated individuals, but not the levels of KLRD1 and PGDFB. sKLRD1 that is involved in the regulation of natural killer cell (NK) mediated cytotoxicity, failed to be restored to the level of HIV-negative individuals despite successful long-term ART. Additional analysis of NK cells along with T-cell subsets can provide insights into the long-term effects of ART on the immune system. Abstract : Supplemental Digital Content is available in the text